2012
DOI: 10.1111/j.1478-3231.2012.02778.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein A2/B1 in association with hTERT is a potential biomarker for hepatocellular carcinoma

Abstract: Heterogeneous nuclear ribonucleoprotein A2/B1, an hTERT-associated protein, is a potential prognostic biomarker for HCC patients and might be a therapeutic target of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…As shown in Figure 7A, direct interaction between hnRNPA2/B1 and p300 were observed in A549, H1299 and H460 cell lines by immunoprecipitation experiments. To further confirm the interaction between p300 and hnRNPA2/B1, we also analyzed the subcellular co-localization of p300 and hnRNPA2/B1 in H460, H322, H1299 cells by immunofluorescence confocal assay, and found that most of hnRNPA2/B1 and p300 proteins colocalized in the cell nuclei of H460 cells ( Figure 7B) and H322, H1299 cells ( Supplementary Figure 4), which are consistent with the previous study (Mizuno et al, 2012).…”
Section: Hnrnpa2/b1 Expression Was Positively Correlated With Cox-2 Esupporting
confidence: 90%
“…As shown in Figure 7A, direct interaction between hnRNPA2/B1 and p300 were observed in A549, H1299 and H460 cell lines by immunoprecipitation experiments. To further confirm the interaction between p300 and hnRNPA2/B1, we also analyzed the subcellular co-localization of p300 and hnRNPA2/B1 in H460, H322, H1299 cells by immunofluorescence confocal assay, and found that most of hnRNPA2/B1 and p300 proteins colocalized in the cell nuclei of H460 cells ( Figure 7B) and H322, H1299 cells ( Supplementary Figure 4), which are consistent with the previous study (Mizuno et al, 2012).…”
Section: Hnrnpa2/b1 Expression Was Positively Correlated With Cox-2 Esupporting
confidence: 90%
“…Its cytoplasmic localization is considered a bona fide biomarker of hepatocellular carcinoma 42,43 or lung cancer. 40,41 This could explain why HNRNPA2B1 is functionally relevant for the studied oncogenic features in PDAC cells with a higher cytoplasmic distribution of this protein (KRASdependent PDAC) rather than for the HNRNPA2B1-nuclear-confined KRAS-independent PDAC (Fig 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 6 specific proteins (Fig S1). We focused on heterogeneous nuclear ribonucleoprotein A2/B1 (hereinafter referred to as HNRNPA2B1) (Mowse score= 3.89e+005; sequence coverage =35 %; peptides matched= 10/108) given the described involvement of its cytoplasmic accumulation in malignancies harboring oncogenic KRAS [40][41][42][43] In order to confirm and further characterize the interaction, co-immunoprecipitation with the active form of the major RAS isoforms was studied. We observed a specific interaction with the K-and N-RAS isoforms, being excluded from the H-RAS (Fig 1A).…”
Section: Identification Of Hnrnpa2b1 As a Novel Oncogenic Kras Interamentioning
confidence: 99%
“…HnRNPA2 colocalizes with telomeric chromatin in the subset of PML bodies that are a hallmark of ALT cells, reinforcing the evidence for hnRNPs having a role in telomere maintenance. HnRNP A2/B1 was recently shown to be associated with human telomerase reverse transcriptase (hTERT) and increase telomerase activity in hepatocellular carcinoma which is a new prognostic biomarker (Mizuno, Honda et al 2012). We therefore believe mitochondrial retrograde signaling induced activation of hnRNPA2 which is a telomere regulatory protein is a possible epigenetic link between mitochondrial functional state and nuclear gene expression and telomere state.…”
Section: Mitochondrial Retrograde Signaling As An Epigenetic Regulmentioning
confidence: 99%